The effect of transcutaneous electrical stimulation of the submental area on the cardiorespiratory response in normal and awake subjects - Alsharifi, Abdulaziz; Kaltsakas, Georgios; Pengo, Martino F.; Parati, Gianfranco; Serna-Pascual, Miquel; Rafferty, Gerrard; Steier, Joerg (Frontiers in Physiology, 2023)
Background Electrical stimulation has recently been introduced to treat patients with Obstructive sleep apnoea (OSA). There are, however, few data on the effects of transcutaneous submental electrical stimulation (TES) on the cardiovascular system. We studied the effect of TES on cardiorespiratory variables in healthy volunteers during head-down-tilt (HDT) induced baroreceptor loading. Method Cardiorespiratory parameters (blood pressure, heart rate, respiratory rate, tidal volume, airflow/minute ventilation, oxygen saturation, and end-tidal CO2/O2 concentration) were recorded seated, supine, and during HDT (50°) under normoxic, hypercapnic (FiCO2 5%) and poikilocapnic hypoxic (FiO2 12%) conditions. Blood pressure (BP) was measured non-invasively and continuously (Finapres). Gas conditions were applied in random order. All participants were studied twice on different days, once without and once with TES. Results We studied 13 healthy subjects (age 29 (12) years, 6 female, body mass index (BMI) 23.23 (1.6) kg·m-2). A three-way ANOVA indicated that BP decreased significantly with TES (systolic: p=4.93E-06, diastolic: p=3.48E-09, mean: p=3.88E-08). Change in gas condition (systolic: p=0.0402, diastolic: p=0.0033, mean: p= 0.0034) and different postures (systolic: 8.49E-08, diastolic: p=6.91E-04, mean: p=5.47E-05) similarly impacted on BP control. When tested for interaction, there were no significant associations between the three different factors electrical stimulation, gas condition, or posture, except for an effect on minute ventilation (gas condition/posture p=0.0369). Conclusion Transcutaneous electrical stimulation has a substantial impact on the blood pressure. Similarly, postural changes and variations in inspired gas impact on blood pressure control. Finally, there was an interaction between posture and inspired gases that affects minute ventilation. These observations have implications on our understanding of integrated cardiorespiratory control, and may prove beneficial for patients with SDB who are assessed for treatment with electrical stimulation.